Throughput model of TCP SACK under burst losses - Zhi-ming WANG; Xiao-ping ZENG; Juan LI; Xue LIU; Li CHEN (Tongxin xuebao)
Describing the end-to-end burst loss characteristics by Gilbert loss model,the model of RFC6675-based fast retransmission was proposed and recovery and a throughput model of TCP SACK based on the fast retransmission and recovery model was derced.The numerical and network simulations show that the fast retransmission and recovery mod-el can accurately describe the fast retransmission and recovery process,the estimation accuracy of throughput model was promoted.